Technology and school social work services: introducing technology in an alternative school. - Pahwa BA (Journal of Technology in Human Services, 2003)
The public school system, one of the largest human service institutions in our nation, is continuously engaged in a struggle to balance the needs of a growing and diverse population with continuing threats of budget cuts. Under these conditions, it becomes even more critical that school social workers understand and appreciate the role of technology in delivering and evaluating services. To assess the effectiveness of school social work services, evaluation will have to be planned for, and systems of data collection and processing will have to be conducted on an ongoing basis.This paper outlines the process whereby school social workers in a local school district proceeded to introduce technology into their service delivery regimen. Secondly, the paper shows how such technology was, and may be, used to evaluate the services provided by school social workers in an alternative school.